"You're made to feel like a dirty filthy smoker when you're not, cigar smoking is another thing all together." Responses of Australian cigar and cigarillo smokers to plain packaging. (25th February 2015) - Miller, Caroline L; Ettridge, Kerry A; Wakefield, Melanie A
Abstract : Objective: To explore experiences of cigar and cigarillo smokers under Australian laws requiring plain packaging (PP) and strengthened graphic health warnings (GHWs). Methods: In February/March 2014, we conducted: in-depth interviews with 10 regular premium cigar smokers; two focus groups with occasional premium cigar and premium cigarillo smokers (n=14); four focus groups with non-premium cigarillo smokers (n=28); and a national online survey of cigar and/or cigarillo smokers (n=268). Results: Premium cigar smokers had limited exposure to PP, with many purchasing fully branded cigars in boxes duty free or online and singles in non-compliant packaging. Those who were exposed noticed and were concerned by the warnings, tried to avoid them and felt more like 'dirty smokers'. Changes in perceived taste, harm and value were minimal for experienced premium cigar smokers. Occasional premium cigar and premium cigarillo smokers with higher PP exposure (gained by purchasing boxes rather than singles) perceived cigar/package appeal and value had declined and noticed the GHWs. Non-premium cigarillo smokers reported high PP exposure, reduced perceived appeal, quality, taste, enjoyment and value, somewhat increased perceived harm, greater noticeability of GHWs and concealment of packs and more contemplation of quitting. Online survey participants reported increased noticeability of GHWs (33%), decreased appeal of packaging (53%) and reduced consumption of cigars (42%) and cigarillos (44%) since PP implementation. Conclusions: Non-premium cigarillo smokers appear to have been most exposed and influenced by PP, with cigar smokers less so, especially regular premium cigar smokers who have maintained access to fully branded products.